Theoretical frameworks informing family-based child and adolescent obesity interventions: A qualitative meta-synthesis. Issue 6 (November 2017) - Alulis, Sarah; Grabowski, Dan
Summary: Background: Child and adolescent obesity trends are rising throughout the world, revealing treatment difficulties and a lack of consensus about treatment. The family system is broadly viewed as a potential setting for facilitation of behaviour change. Therefore, family-based interventions have come into focus. However, the use of theoretical frameworks to strengthen these interventions is rare and very uneven. Objective and method: To conduct a qualitative meta-synthesis of family-based interventions for child and adolescent obesity to identify the theoretical frameworks applied, thus understanding how theory is used in practice. A literature review was conducted between January and March 2016. A total of 35 family-based interventions were selected for analysis. Results: Eleven interventions explicitly stated that theory guided the development and were classified as theory-inspired. The social cognitive, self-efficacy and Family Systems Theory appeared most frequently. The remaining 24 were classified as theory-related as theoretical elements of self-monitoring; stimulus control, reinforcement and modelling were used. Conclusion: The designs of family-based interventions reveal numerous inconsistencies and a significant void between research results and health care practice. Based on the analysis, this article proposes three themes to be used as focus points when designing future interventions and when selecting theories for the development of solid, theory-based frameworks for application. The themes are: (1) age of target group, (2) intervention objective, and (3) self-efficacy and readiness for change.